Molecular modelling of polypropylene crystallization: article - Ahmad Azmi, Aini Shafinaz; Sharudin, Rahida Wati Sharudin (2017)
Polypropylene is a semicrystalline polymer where crystallinity is usually in the range 40-70% and it also depends on the level of tacticity of the polymer.. Different crystal modifications can exist depending on the condition of the crystallization process and isotacticity of polypropylene. These changes also create differences in strength, heat resistance and pressure bonding properties. Materials Studio software package is used for the simulation of polypropylene. The molecular simulation is carried out using the forcite module, using the Condensed-phase Optimized Molecular Potentials for Atomistic Simulation Studies (COMPASS) force field. The limitation of this research was only isotactic polypropylene was investigated in this paper. In conclusion, the growth of spherulite or the crystallization of polypropylene can be affected by the cooling rates, temperature, tacticity and many more. However as for isotactic propylene, a few types of spherulites can be formed based on the condition of the crystallization process.